AMIR TIMUR AND THE HISTORY OF MINIATURE AND FINE ART OF THE TIMURI PERIOD (Academicia Globe: Inderscience Research, 2023)
This article summarizes the history of miniature and fine art of Amir Temur and the Timurid period, its specific aspects, and information on the fine and miniature works created in this period.